Information and Husband’s Support on Implementation Postpartum Gymnastics during COVID 19 Pandemic in Indonesia - Windarti, Yunik; Anggasari, Yasi; Hasina, Siti Nur; Firdaus, Firdaus (Open Access Macedonian Journal of Medical Sciences, 2021)
Background : The practice of postnatal gymnastics in Indonesia is still little done by postpartum mothers both before and during the covid pandemic 19. Some of the contributing factors include lack of knowledge about postnatal gymnastics, fatigue, and the mother’s mindset about the importance of postnatal gymnastics for health which is still lacking. Post-delivery exercise can help mothers to get back to their normal health as they were before pregnancy. Objective : This study aims to analyze the effect of information and husband’s support on the implementation postnatal gymnastics during the covid 19 pandemic. Methods : Non-experimental research design: cross sectional analytic, the independent variable is husband’s information and support and the dependent variable is postpartum exercise. This research was conducted in April – August 2021. The population of postpartum mothers was 102, the sampling technique was incidental sampling in Wonokromo Village, Surabaya, East Java, Indonesia. Research instrument with a questionnaire. The data were analyzed using the Multiple Logistics Regression test. Results : The results showed that partially there was a significant effect of husband’s support (p = 0.013) on postnatal exercise, but for information during the pandemic there was no effect (p = 0.998) on postpartum exercise. The results of the analysis showed that the OR value of the information was 1.615E9 (95%CI: 0.000 – 0.000) and the OR of husband’s support was 3.385 (95%CI: 1.289 – 8.886). Conclusion : Husband’s support during the covid 19 pandemic affects mothers in doing postnatal exercise. Obtaining information about postnatal exercise during the COVID-19 pandemic does not affect the mother in its implementation.